2000
DOI: 10.1097/00003246-200009000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Use of hypertonic saline solutions in treatment of cerebral edema and intracranial hypertension

Abstract: HS demonstrates a favorable effect on both systemic hemodynamics and intracranial pressure in both laboratory and clinical settings. Preliminary evidence supports the need for controlled clinical trials evaluating its use as resuscitative fluid in brain-injured patients with hemorrhagic shock, as therapy for intracranial hypertension resistant to standard therapy, as firstline therapy for intracranial hypertension in certain intracranial pathologies, as small volume fluid resuscitation during spinal shock, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
176
2
12

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(191 citation statements)
references
References 118 publications
1
176
2
12
Order By: Relevance
“…Sodium has a higher reflection coefficient than does mannitol. 17 Consequently, hypertonic saline acts as a dehydrating agent; it has been demonstrated that hypertonic saline promptly reduces brain water content in experimental models of brain injury and successfully reduces ICP and tentorial herniation in both patients and animals with resistant IH. 17,18 To our knowledge, the current study is the first to use hypertonic saline in the management of IH and in the prevention of cerebral edema for patients with ALF.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium has a higher reflection coefficient than does mannitol. 17 Consequently, hypertonic saline acts as a dehydrating agent; it has been demonstrated that hypertonic saline promptly reduces brain water content in experimental models of brain injury and successfully reduces ICP and tentorial herniation in both patients and animals with resistant IH. 17,18 To our knowledge, the current study is the first to use hypertonic saline in the management of IH and in the prevention of cerebral edema for patients with ALF.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertonic saline avoids the diuretic effect of mannitol while still being effective at reducing brain water. After administration, cerebral perfusion may actually be increased [27]. Various concentrations are clinically used, with as much as 30 mL boluses of 23.4% saline in a single dose.…”
Section: Osmotherapymentioning
confidence: 99%
“…The mechanisms of cerebral edema in the nonischemic hemisphere after focal ischemia are complex and not completely elucidated, but possibly include impedance of cerebral venous return from cerebral swelling, intrahemispheric diaschisis (Abe et al, 2000), increased BBB permeability by inflammatory mediators (Abbott, 2000), neurohumoral responses (Bemana and Nagao, 1999), induction of proteins, such as VEGF (van Bruggen et al, 1999), and upregulation of aquaporin-4 (Taniguchi et al, 2000). Hypertonic saline solutions have received renewed attention as hyperosmolar agents and are being increasingly used clinically as a therapeutic modality for cerebral edema in a variety of brain injury paradigms (Bhardwaj and Ulatowski, 2004;Harukuni et al, 2002;Qureshi and Suarez, 2000; Figure 3 Water content in the 6 predetermined brain subregions from rats subjected to 2-h MCAO and treated with NS, 20% mannitol, 3% HS, and 7.5% HS. (A) Water content (%) in three brain regions (a to c) from the ipsilateral ischemic hemisphere.…”
Section: Cerebral Edema After Ischemic Strokementioning
confidence: 99%
“…Osmotherapy is the cornerstone of medical therapy for cerebral edema (Bhardwaj and Ulatowski, 2004;Harukuni et al, 2002;Qureshi and Suarez, 2000;Paczynski, 1997;Schell et al, 1996). Acute administration of osmotic agents produces a potent antiedema action, primarily on undamaged brain regions with an intact blood-brain barrier (BBB), theoretically causing egress of water from the interstitial and extracellular space into the intravascular compartment, thereby improving intracranial elastance (Bhardwaj and Ulatowski, 2004;Harukuni et al, 2002;Qureshi and Suarez, 2000;Paczynski, 1997;Schell et al, 1996). In addition to causing 'dehydration' of the brain, osmotic agents exert beneficial nonosmotic cerebral effects, such as augmentation of cerebral blood flow (CBF), resulting in enhanced oxygen delivery, free radical scavenging, and diminished formation, and enhanced reabsorption of cerebrospinal fluid (Schmoker et al, 1991;Bhardwaj and Ulatowski, 2004;Harukuni et al, 2002;Qureshi and Suarez, 2000;Paczynski, 1997;Schell et al, 1996;Prough et al, 1991;Toung et al, 2002).…”
Section: Introductionmentioning
confidence: 99%